Carbon mitigation potential of the airport-based solar PV plants in the Indian context - S., Sreenath; Sudhakar, K.; Ahmad Fitri, Yusop (Taylor & Francis, 2019)
The atmospheric pollution from the aviation industry can be decreased through the consumption of Renewable Energy (RE)-based electricity generation for airport operations. Among the various RE technologies, the solar PV system is most suitable in the airport environment. The technical performance of the solar PV system installed on the premises of ten Indian airports for onsite electricity generation is analysed in the present study. These airports are Kolkata, Kochi, Delhi, Hyderabad, Bengaluru, Jaipur, Chennai, Mumbai, Calicut, and Vadodara. Using PV software, it was found that the airport’s solar PV system operates with a performance ratio of around 75% and the capacity factor between 16.5% and 18.8%. In addition to that, the Green House Gas mitigation potential and corresponding cost savings in terms of Certified Emission Reduction (CER) are estimated for each airport. With more than 400 aerodromes, the potential for airport’s solar PV projects is enormous in the Indian scenario.